Kampung Jamu: Pilar Peningkatan Kemampuan Bersaing Kota Semarang - Eko Nursanty; Djudjun Rusmiatmoko; Wawan Destiawan; Muhammad Fahd Diyar Husni; Yuliati Yuliati (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2023)
Enhancing a city's competitiveness in the era of globalization requires harnessing local potential, particularly traditional health remedies. These remedies encapsulate unique knowledge of natural ingredients and healing techniques proven effective over centuries. Promoting the utilization and development of traditional health recipes not only enriches local culture but also improves the quality of life for communities. Cities can leverage their cultural and natural heritage by creating new economic opportunities through industries based on traditional health remedies, such as herbal products and natural medicines. In the long run, this contributes to the city's economic growth and competitiveness across various sectors. Empowering local potential through traditional health recipes is a sustainable strategy for winning the urban competition, enriching local culture, and promoting sustainable economic development by blending local wisdom with modern innovation.